Characterization of a triad of genes in cyanophage S-2L sufficient to replace adenine by 2-aminoadenine in bacterial DNA - Dariusz Czernecki (Nature Portfolio, 2021)
The cyanophage S-2L incorporates 2-aminoadenine (Z) instead of adenine into its DNA, which still pairs with thymine forming a triple hydrogen bond. Here, the authors identify a third gene mazZ located between purZ and datZ that is required for 2-aminoadenine biosynthesis and determine the crystal structures of MazZ and PurZ. They further show that co-expression of these three genes in E.coli enables 2-aminoadenine incorporation into the bacterial genome.